“Fascist Architecture” In Spain? A Discussion on Its Conceptual Appropriateness and Its Factual Development In Post-War Spain. - Almonacid Canseco, Rodrigo (Revista de Historia Social y de las Mentalidades, 2024)
The historiography of 20th-century architecture has systematically avoided using the term “fascist architecture” in the case of Spain, unlike its counterparts “Nazi architecture” in Germany or “Fascist architecture” in Italy. A discussion is held on whether or not this conceptualisation is relevant, and four approaches to the problem are proposed: ultra-nationalism, palingenesis, totalitarianism, and Catholicism. The results show that Spanish architecture between 1931 and 1953 provides theoretical and material evidence of the process of fascistisation before and during the Spanish Civil War, and subsequently its slow de-fascistisation thanks to professional contact with the international environment and to the singular factor of national Catholicism.
Keywords: Fascist Architecture; History of Architecture; Francoism; National-Catholicism; Spanish Fascism